1996
DOI: 10.1007/bf00194087
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-impurity incorporation during the growth of epitaxial group III?V materials

Abstract: This paper is a review of the incorporation and behaviour of carbon in group III-V materials. Both vapour phase epitaxy and growth in ultra high-vacuum environments are covered. Particular attention is given to the factors which influence the carbon-uptake rate such as the growth temperature, ratio of group V to group III materials and parasitic interaction with other species at the growth front. Among the latter, the role of hydrogen is crucial not only to the understanding of the incorporation of carbon but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…N-content was controlled by [DMHy]/([TBP]+[DMHy]) ratio. The C concentration of III-V materials was found to increase with decreasing substrate temperature and V/III ratio [10]. In the growth of GaPN, Geisz et al [9] has been reported that C is unintentionally incorporated from organometallic sources (TEGa and DMHy) in OMVPE-grown GaPN and it acts as acceptor.…”
Section: Methodsmentioning
confidence: 97%
“…N-content was controlled by [DMHy]/([TBP]+[DMHy]) ratio. The C concentration of III-V materials was found to increase with decreasing substrate temperature and V/III ratio [10]. In the growth of GaPN, Geisz et al [9] has been reported that C is unintentionally incorporated from organometallic sources (TEGa and DMHy) in OMVPE-grown GaPN and it acts as acceptor.…”
Section: Methodsmentioning
confidence: 97%
“…While GaAs can be readily doped with shallow acceptors such as C to produce hole densities of around 10 21 cm À3 [92] and the Mn acceptors also contribute holes, the p-doping levels in GaN are limited to much lower values under normal conditions. For example, the ionization level (E a ) of the most common acceptor dopant in GaN, namely Mg, is relatively deep in the gap (E v þ 0:17 eV).…”
Section: Mechanisms Of Ferromagnetismmentioning
confidence: 99%
“…Carbon is a known low-diffusivity impurity atom in III-V materials, which may be unintentionally incorporated during metalorganic based epitaxy; the polarity and concentration vary with specific grown materials and precursors, and growth conditions. [24][25][26][27][28] Considering that NW sidewalls are exposed to MO material during the entire growth process (moreover, usually growth precursors diffuse along the sidewalls to reach the catalyst), [29][30][31][32] it is reasonable to assume a high unintentional carbon sidewall concentration in such growth systems (MOVPE and MOMBE). Figure 5 shows band diagrams for the exponential doping profile.…”
Section: Resultsmentioning
confidence: 99%